Effects of dietary thyme essential oil on blood haematobiochemical, redox status, immunological and reproductive variables of rabbit does exposed to high environmental temperature - Sameh A. Abdelnour; Ibrahim T. El-Ratel; Soliman I. Peris; Ali Ali El-Raghi; Sara F. Fouda (Italian Journal of Animal Science, 2022)
Dietary manipulations play an important role in improving the rabbit behaviour and performance and mitigating the negative effects of heat stress (HS) in rabbits. Thus, this study was designed to determine the modulatory role of thyme essential oil (TEO) in improving the blood metabolites, antioxidant status, immunological response, ovarian activity, reproductive traits and fecundity of rabbit does kept under high environmental stress. A total of 100 nulliparous does were used and randomly assigned into five treatments of 20 does each. The basal diet fed to the experimental groups contained TEO at levels of 0, 50, 100, 150 and 200 mg/kg diet for the 1st, 2nd, 3rd, 4th and 5th groups, respectively. The period of TEO treatment was one month during an experimental period of three months during the summer season. Results showed that TEO at a level of 100 mg/kg diet decreased (p ≤ .001) MDA, while increased (≤.001) total proteins (TPs), albumin (AL), globulin (GL), blood haemoglobin, total antioxidant capacity (TAC), haematocrit (Ht) and glutathione (GSH). Conversely, the TEO treatment did not affect GSH peroxidase and superoxide dismutase (SOD). Immunological variables (IgG and IgM), milk production, ovulation rate (OR) and normal embryos percentage were significantly improved by 100 mg TEO/kg diet supplementation. The reproductive variable of stressed rabbit does fed TEO were significantly higher than those in the control diet. Collectively, dietary TEO supplementation can alleviate the negative influences of heat stressed-female rabbits, via enhancing the antioxidant capacity and immunological parameters.Highlights Dietary manipulations play an important role in improving the rabbit behaviour and performance. Addition of TEO to rabbit diets improved rabbit performance and health as well as reduced the negative effects of heat stress (HS). Immunological indices and milk production, ovulation rates (ORs) and normal embryos were significantly improved by TEO. Thyme essential oil (TEO) decreased MDA and increased protein and its fraction, blood haemoglobin and total antioxidant capacity (TAC).